Governance, Transparency, and Financial Regulation in the Global Digital Economy - Isabella Rose M Harding (PT. Islamic Research Publisher, 2025)
The rapid expansion of the global digital economy has fundamentally transformed financial transactions, business models, and cross-border economic interactions, while simultaneously creating complex governance and regulatory challenges. This study aims to examine how governance quality, transparency mechanisms, and financial regulation interact to promote accountability, market integrity, and sustainable growth within the global digital economy. Employing a qualitative field research design, the study collected primary data through semi-structured interviews with financial regulators, fintech practitioners, digital entrepreneurs, and policy experts, complemented by direct observations and analysis of institutional documents and regulatory frameworks. The collected data were analyzed using thematic analysis involving data reduction, categorization, interpretation, and cross-source triangulation to ensure the credibility and validity of the findings. The results demonstrate that effective governance in the digital financial ecosystem depends on the integration of transparent regulatory institutions, adaptive legal frameworks, technological innovation, and collaborative stakeholder engagement. Regulatory fragmentation, inconsistent transparency standards, data privacy concerns, and the rapid evolution of financial technologies remain significant barriers to achieving regulatory effectiveness across jurisdictions. Furthermore, the findings reveal that digital governance mechanisms supported by regulatory technology, real-time monitoring systems, and international regulatory cooperation substantially improve public trust, reduce compliance risks, and strengthen financial resilience in increasingly interconnected markets. The study also highlights that governance effectiveness is influenced not only by formal legal institutions but also by organizational accountability, ethical digital practices, and institutional capacity to respond to technological disruption. This research contributes to the literature by providing an empirically grounded framework that integrates governance, transparency, and financial regulation within the context of the global digital economy. The findings offer practical policy recommendations for governments, regulatory authorities, and international organizations seeking to establish adaptive, transparent, and resilient digital financial governance capable of supporting sustainable economic development.